2018
DOI: 10.1002/rra.3366
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat use of native fishes in the Kootenai River: A fine‐scale evaluation of large‐scale habitat rehabilitation efforts

Abstract: Fish and microhabitat data were collected at 542 prepositioned electrofishing sites (surface area of each site = 4 m2) in the Kootenai River, Idaho, during 2014 and 2015 to evaluate small‐scale habitat use by fishes, as it relates to large‐scale habitat rehabilitation efforts. Samples were collected from a 12‐km braided segment of river that had received localized habitat rehabilitation treatments since 2011. Fish and microhabitat data were collected to investigate habitat drivers related to the occurrence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 79 publications
(113 reference statements)
0
12
0
Order By: Relevance
“…Field surveys have demonstrated that juvenile largescale sucker use areas with slow current velocities (Branigan et al, 2018), and slow current velocity habitats are generally associated with the presence of pumpkinseed (Wydoski & Whitney, 2003). Although backwater habitats in the Kootenai River are scarce, they provide important habitat for smallbodied native fishes, including juvenile largescale sucker (Branigan et al, 2018). Given the pumpkinseed's affinity for lentic environments and the evidence surrounding their use of low-velocity habitats, backwaters likely provide suitable habitat for pumpkinseed in et al, 2018;Smith et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Field surveys have demonstrated that juvenile largescale sucker use areas with slow current velocities (Branigan et al, 2018), and slow current velocity habitats are generally associated with the presence of pumpkinseed (Wydoski & Whitney, 2003). Although backwater habitats in the Kootenai River are scarce, they provide important habitat for smallbodied native fishes, including juvenile largescale sucker (Branigan et al, 2018). Given the pumpkinseed's affinity for lentic environments and the evidence surrounding their use of low-velocity habitats, backwaters likely provide suitable habitat for pumpkinseed in et al, 2018;Smith et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although backwater habitats in the Kootenai River are scarce, they provide important habitat for smallbodied native fishes, including juvenile largescale sucker (Branigan et al, 2018). Given the pumpkinseed's affinity for lentic environments and the evidence surrounding their use of low-velocity habitats, backwaters likely provide suitable habitat for pumpkinseed in et al, 2018;Smith et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations